Effects of the selected cytochrome P450 oxidoreductase genetic polymorphisms on cytochrome P450 2B6 activity as measured by bupropion hydroxylation. Issue 2 (February 2016) - Lv, Jinfeng; Hu, Lei; Zhuo, Wei; Zhang, Congmin; Zhou, Honghao; Fan, Lan
Abstract : Background/Aim: Cytochrome P450 oxidoreductase (POR) is required for drug metabolism by all microsomal cytochrome P450 (CYP) enzymes. The aim of this study was to investigate whether single-nucleotide polymorphisms in the POR gene were correlated with interindividual variations in CYP2B6 activity, as measured by bupropion hydroxylation. Methods: Thirty-five healthy individuals with selected CYP2B6 and POR polymorphisms were involved in the clinical study. The activity of CYP2B6 was evaluated on the basis of the area under the time–concentration curve (AUC) ratio of hydroxybupropion versus bupropion (AUC_hyd/AUC_bup). Results: Individuals carrying CYP2B6*1/*1 showed a significantly higher mean AUC_hyd/AUC_bup than individuals carrying the CYP2B6*1/*6 and CYP2B6*6/*6 variants (17.1±6.23 vs. 10.3±4.53, P =0.003 and 17.1±6.23 vs. 9.41±2.84, P =0.002, respectively). POR g.6593A>G (rs2868177) AA homozygotes showed a significantly lower mean AUC_hyd/AUC_bup than POR g.6593A>G AG heterozygotes or GG homozygotes (8.54±2.65 vs. 14.9±6.06, P =0.005 and 8.54±2.65 vs. 16.8±6.45, P =0.002, respectively). Moreover, POR g.6593A>G AA homozygotes had a significantly lower mean AUC_hyd/AUC_bup than the POR g.6593A>G AG/GG genotypes in the CYP2B6*1/*1, CYP2B6*1/*6 and CYP2B6*6/*6 groups (10.9± 1. 82 vs. 19.7±5.53, P <0.001; 6.18±0.284 vs. 12.1±4.31, P =0.011; and 6.94±1.48 vs. 10.9±2.39, P =0.043, respectively). There was no significant difference in the mean AUC_hyd/AUC_bup among different POR c.1508C>T ( *28 or rs1057868) genotypes, even after the effect of CYP2B6*6 was excluded. Conclusion: These results indicate, for the first time, that the POR g.6593A>G polymorphism significantly influences CYP2B6 activity, as measured by bupropion hydroxylation, in humans, and the CYP2B6*6 and POR g.6593A>G polymorphisms might be considered simultaneously for the individualized therapy with CYP2B6 substrate drugs such as bupropion.